Using a Clinical Surveillance System to Detect Drug‐Associated Hypoglycemia in Nursing Home Residents. Issue 10 (12th October 2015) - Culley, Colleen M.; Perera, Subashan; Marcum, Zachary A.; Kane‐Gill, Sandra L.; Handler, Steven M.
<x xml:space="preserve">Abstract</x> Objectives To determine whether a clinical surveillance system could be used to detect drug‐associated hypoglycemia events and determine their incidence in nursing home (NH) residents. Design Retrospective cohort. Setting Four NHs in western Pennsylvania. Participants Any resident of the four NHs who had a computer‐generated alert detecting potential drug‐associated hypoglycemia over a 6‐month period were included. Measurements Descriptive statistics were used to summarize all variables, including the frequency and distribution of alert type according to glucose threshold. Analyses were conducted according to numbers of alerts and residents. The medications associated with the drug‐associated hypoglycemia alerts were identified, and frequency of their inclusion in alerts was calculated. Additional calculations included time to drug‐associated hypoglycemic event alert from date of admission and frequency of events associated with postacute, short‐stay (≤35 days) admissions. Results Seven hundred seventy‐two alerts involving 141 residents were detected. Ninety (63.8%) residents had a glucose level of 55 mg/dL or less, and 42 (29.8%) had a glucose level of 40 mg/dL or less. Insulin orders were associated with 762 (98.7%) alerts. Overall incidence of drug‐associated hypoglycemia events was 9.5 per 1, 000 resident‐days. Conclusion Hypoglycemia can be detected using a clinical surveillance system. This evaluation found a high incidence of drug‐associated hypoglycemia in a general NH population. Future studies are needed to determine the potential benefits of use of a surveillance system in real‐time detection and management of hypoglycemia in NHs.